The Impact of Sexual Orientation on Sexuality and Sexual Practices in North American Medical Students - Breyer, Benjamin N. (2010)
INTRODUCTION: There has been limited investigation of the sexuality and sexual dysfunction in non-heterosexual subjects by the sexual medicine community. Additional research in these populations is needed. AIMS: To investigate and compare sexuality and sexual function in students of varying sexual orientations. METHODS: An internet-based survey on sexuality was administered to medical students in North American between the months of February and July of 2008. MAIN OUTCOME MEASURES: All subjects provided information on their ethnodemographic characteristics, sexual orientation, and sexual history. Subjects also completed a series of widely-utilized instruments for the assessment of human sexuality (International Index of Erectile Function [IIEF], Female Sexual Function Index [FSFI], Premature Ejaculation Diagnostic Tool [PEDT], Index of Sex Life [ISL]). RESULTS: There were 2,276 completed responses to the question on sexual orientation. 13.2% of male respondents and 4.7% of female respondents reported a homosexual orientation; 2.5% of male and 5.7% of female respondents reported a bisexual orientation. Many heterosexual males and females reported same-sex sexual experiences (4% and 10%, respectively). Opposite-sex experiences were very common in the male and female homosexual population (37% and 44%, respectively). The prevalence of premature ejaculation (PEDT > 8) was similar among heterosexual and homosexual men (16% and 17%, P = 0.7, respectively). Erectile dysfunction (IIEF-EF < 26) was more common in homosexual men relative to heterosexual men (24% vs. 12%, P = 0.02). High risk for female sexual dysfunction (FSFI < 26.55) was more common in heterosexual and bisexual women compared with lesbians (51%, 45%, and 29%, respectively, P = 0.005). CONCLUSION: In this survey of highly educated young professionals, numerous similarities and some important differences in sexuality and sexual function were noted based on sexual orientation. It is unclear whether the dissimilarities represent differing relative prevalence of sexual problems or discrepancies in patterns of sex behavior and interpretation of the survey questions.